Programa de recreación como derecho del buen vivir en los niños /as de 4 a 5 años del primer año de educación básica del paralelo ¨E¨ en la escuela “Isidro Ayora” de la parroquia La Matriz, cantón Latacunga, provincia Cotopaxi, año lectivo 2014-2015 - Martínez Uribe, Blanca Sofía (2015)
This research was performed in order to make known the recreation and activities goal which are necessary to benefit the infants development process during the teaching-learning process. On the findings, they should be considered a thematic content in order to understand the problem clearly. They are: the recreation importance, recreation in the teaching-learning process. So, the teachers and parents’ role in the recreation and children attitudes against recreational activities. Additionally, recreational activities that parents and teachers offer depend on the sharing experiences inside and outside home and school time. For this reason, we hold in conducting interviews, surveys and mainly realization of a recreation program for all people who are involved in the child development.